Contracting on Ambiguous Prospects. (5th April 2017) - Amarante, Massimiliano; Ghossoub, Mario; Phelps, Edmund
Abstract : We study contracting problems where one party perceives ambiguity about the relevant contingencies. We show that the party who perceives ambiguity has to observe only the revenue/loss generated by the prospect object of negotiation, but not the underlying state. We, then, introduce a novel condition (vigilance), which extends the popular monotone likelihood ratio property to settings featuring ambiguity. Under vigilance, optimal contracts are monotonic and, thus, produce the right incentives in the presence of both concealed information and hidden actions. Our result holds irrespectively of the party's attitude towards ambiguity. Sharper results obtain in the case of global ambiguity‐loving behaviour.